Pengaruh Media Tanam terhadap Pertumbuhan Tanaman Kedelai Hitam (Glicine Max L ) dengan Sistem Vertikultur - Wiwin Tiana Siregar; Rahmadina Rahmadina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine how the effect of the growth of black soybean plants (Glycine max L.) with a verticulture system. This research was conducted on Jl. Ekarasmi Gg. Ekanusa III Kec. Medan Johor, Medan City, from September to November 2022. This study used a non-factorial randomized block design (RBD) consisting of one treatment factor with 3 levels and 6 repetitions, namely: M1 = 2 kg soil, M2 = 2: 1 (2 kg soil + 1 kg rice husk), and M3 = 2:1 (2 kg soil + 1 kg cocopeat). This research was designed by doing 6 repetitions. The parameters used in this study were plant height, leaf area index, total and total chlorophyll a b content, relative growth rate, N uptake, and number of root nodules. The results of this study were that the planting medium had a significant effect on almost every parameter but the planting medium had no significant effect on one parameter, namely N nutrient uptake, with levels of M1 and M3. From the results of the study, it can be concluded that the application of planting media to the vegetative growth of black soybeans has an influence on the vegetative growth of black soybeans on almost all parameters, but on the parameters of nutrient absorption, black soybeans have no real effect with planting horticulture systems.